A Flexible Self‐Powered Sensing Element with Integrated Organic Thermoelectric Generator. Issue 8 (29th May 2019) - Zheng, Chengzhi; Xiang, Lanyi; Jin, Wenlong; Shen, Hongguang; Zhao, Wenrui; Zhang, Fengjiao; Di, Chong‐an; Zhu, Daoben
Abstract: Flexible self‐powered sensing electronics are required to promote the development of wearable and portable electronics. Although self‐powered sensing elements with individual devices, such as piezoelectric and thermoelectric devices, have been demonstrated, it is challenging to realize self‐powered operation for most sensing applications. In this work, a flexible self‐powered sensing element is developed by integrating organic‐transistor‐based chemical sensors with a flexible power supplier, an organic thermoelectric (OTE) generator. The constructed OTE array on a paper substrate shows a maximum open‐circuit voltage of 0.52 V and a maximum power output of 0.32 µW. Notably, the device can power organic field‐effect transistor‐based gas sensors with ultralow operating voltage. The integrated element shows sensitive ammonia detection behavior without an additional power supply. This work suggests that OTE devices are good candidates as flexible power sources, and can be implemented in new strategies for developing self‐powered electronics through device integration. Abstract : A flexible self‐powered sensing element with a paper‐substrate‐based thermoelectric generator and an organic‐transistor‐based sensor is fabricated. The thermoelectric array exhibits a robust power output with a maximum open‐circuit voltage of 0.5 V, which further powers an ultralow‐power‐consumption sensing transistor with a detection limit for ammonia of 1 ppm.